Electrochemical Removal of Nitrogenous Compounds in Relation to Concentration of Chloride Ions of Micro-Polluted Water - Wang, Hao; Zhang, Yaozong; You, Zhiguo (Asian Journal of Chemistry, 2015)
Micro-polluted water was treated by electrochemical oxidation method in this work. When the plate distance was 1 cm and electrolysis time was 10 min, NaCl solution was added to the reaction equipment, which made the ratios of concentration of NH4+ and Cl– were 1:1, 1:2 and 1:3, respectively. The removal effects on nitrogenous compounds of the change of the chloride concentration in the water by electrochemical method were investigated. The results revealed that the higher the chloride concentration in the water, the higher the removal rate to nitrogenous compounds, along with the increase of cell voltage, the removal rates of nitrogenous compounds increased too. Considering the power consumption per ton wastewater and other factors, the optimal running conditions of this experiment were the cell voltage 6 V and the ratio of concentration of NH4+ and Cl– were 1:3.